Nail gun injury through the parapharyngeal space in a carpenter: a unique case report - Alswaiheb, Jameel N.; Motiwala, Mohammad Ali; Ahmed, Muhammad Wasi; Beidas, Tala Fawwaz (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
In developing countries, head and neck penetrating injuries from construction nails are rare can be dangerous or fatal. The use of nail guns in the construction industry gained popularity during the 1990s and is now widespread. In majority of nail gun injuries, the extremities are involved, although injuries to the head and neck region have also been described with approximately 45 cases of cranium penetrating nail gun injuries published in the literature. The management of such cases includes a neurological examination, systemic physical examination, and determination of the optimal surgical method to approach and remove the foreign body. we report a case of penetrating skull base injury caused by a nail gun in a 46-year-old man that was successfully managed by a transnasal endoscopic approach. The patient recovered completely and was discharged. To prevent complications and achieve the best outcomes in such cases, careful diagnosis and assessment are necessary.